Composite phase change energy storage material taking lithium slag-based geopolymer microspheres as carrier and preparation method of composite phase change energy storage material

Prepare porous geological polymer microspheres through lithium residue, and combined with high -thermal guidance materials, successfully packaged organic phase transformer materials, prepared high -performance composite phase transformer energy storage materials, solved the problem of waste and environmental pollution of residue resources, realized The high value -added of lithium residue.

CN119331573AActive Publication Date: 2025-01-21CHENGDU UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411443239.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-21
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The traditional lithium-ion extraction process of lithium salts produces a large amount of lithium slag, resulting in waste of resources and environmental pollution. At the same time, the existing technology has not yet effectively utilized lithium slag for high-value-added resource utilization.

Method used

Use lithium residue to prepare geological polymer microspheres with a porous structure, and modify the high thermal material such as nano -grade graphite to strengthen the heat transfer effect of the ground polymer microspheres. Materials, prepare composite phase change energy storage materials.

Benefits of technology

It significantly improves the heat transfer performance and thermal stability of composite phase change materials, realizes high value-added utilization of lithium slag, and solves the problems of resource waste and environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119331573A_ABST
    Figure CN119331573A_ABST
Patent Text Reader

Abstract

The invention provides a composite phase change energy storage material taking geopolymer (geopolymer) microspheres prepared from spodumene lithium extraction tailings (lithium slag) as a carrier and a preparation method of the composite phase change energy storage material, the geopolymer microspheres are prepared by a dispersion suspension method, and after the geopolymer microspheres are rinsed, dried and calcined, the composite phase change energy storage material is prepared by heating and vacuum impregnation. The phase change energy storage material is stably encapsulated in the geopolymer microspheres, so that the shaped composite phase change energy storage material is obtained. The invention not only provides a phase change energy storage material with large heat storage capacity, excellent packaging performance, good chemical stability, strong leakage resistance, strong cycle stability, strong heat conduction capability and good photothermal conversion capability, but also provides a novel high-added-value utilization mode of spodumene lithium extraction tailings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material technology, relates to a composite phase change energy storage material with geopolymer (geopolymer) microspheres as carriers and a preparation method thereof, and also proposes a high value-added resource utilization method for spodumene lithium extraction tailings (lithium slag). Background Art

[0002] In the development of the new energy industry, lithium salt is the key source material for realizing electrochemical energy storage, and its source is mainly spodumene roasted with sulfuric acid. However, this traditional process will produce a large amount of residual tailings after lithium extraction, referred to as lithium slag, during the manufacturing process, which not only causes waste of resources, but also brings considerable pollution to the environment. Therefore, it is of great significance to explore the effective recovery and reuse of lithium slag. Regarding the application of lithium slag, predecessors have mainly made the following explorations. Zhang Hongquan et al. (2021) used lithium slag as the main raw material to prepare a foam ceramic material with uniform pore distribution and suitable pore size. The compressive strength is 4.14MPa and the thermal conductivity is 0.282W·m -1 ·K -1 . The main chemical elements of lithium slag include Si and Ca. By precisely adjusting the element ratio in the raw materials, lithium slag can be converted into raw materials for cement production, thereby realizing the resource utilization of tailings and promoting environmental protection and sustainable development. Quan Zonggang et al. (2022) used lithium slag as the main siliceous raw material to prepare autoclaved aerated concrete blocks, and studied the effects of ball milling time, formula, static curing time and static temperature on the dry density, compressive strength and other properties of autoclaved aerated concrete blocks. Finally, the optimal formula for preparing concrete with lithium tailings was studied. Wu Ji et al. (2021) used lithium slag as the main raw material to research and develop a lithium slag-based insulation board with low thermal conductivity, high strength, adjustable size and long life. It has excellent thermal insulation performance and light weight, and has broad application prospects in the field of building materials. The above inventions all provide good ideas for the utilization of lithium slag.

[0003] Geopolymers, referred to as geopolymers, are mainly amorphous materials with a three-dimensional network structure formed by the alkali-induced reaction of active silicon-aluminum raw materials, which are connected by bridge O. They are regarded as a new type of green and environmentally friendly mineral cementitious material. The main chemical components of lithium slag are SiO2 and Al2O3, so it can be used to prepare geopolymers. For example, Lemougna et al. (2020) used 20% kaolinite + 80% lithium slag as raw materials to prepare geopolymers, whose 7d compressive strength reached nearly 50MPa, and the high temperature stability could reach 1100-1200℃, with good performance and functional uses. However, how to achieve high added value utilization of lithium slag based on the excellent characteristics of geopolymers is one of the important hotspots in the current research on lithium slag treatment.

[0004] On the other hand, the energy crisis is one of the most important problems facing human society. Energy storage technology significantly improves energy utilization efficiency by solving the contradiction between energy supply and demand in time and space, and thus becomes one of the important technical means to solve energy and environmental problems, among which thermal energy storage is one of the important ways. According to different heat storage principles, heat storage technology is divided into sensible heat storage, latent heat storage and chemical heat storage. Latent heat storage is the use of a large amount of latent heat absorbed and released during the phase change process of phase change materials to store energy, that is, the heat storage process is the process of phase change of materials by melting or solidification. Compared with other heat storage technologies, it has the advantages of high heat storage density, recyclable and green environmental protection. Phase change energy storage materials refer to materials that can absorb and release a large amount of latent heat during the phase change process, including organic phase change materials and inorganic phase change materials. Among them, organic phase change materials such as paraffin and polyethylene glycol have the advantages of high heat storage efficiency, small temperature change and low cost, and have very broad application prospects.

[0005] However, organic phase change materials often have problems such as poor thermal conductivity and liquid leakage during the process of heat storage and release. They cannot be used directly alone. Usually, it is necessary to adopt the technology of shaped phase change heat storage materials. Organic phase change materials and high thermal conductivity and high stability packaging materials are combined into shaped composite phase change materials through certain methods. At present, the preparation methods of composite phase change materials mainly include: microcapsule method, porous inorganic carrier method, sol-gel method, pressing and sintering method and melt blending method, which can effectively solve the leakage problem of organic phase change materials. Among them, the porous inorganic carrier method mainly utilizes the large specific surface area of ​​porous media, the capillary effect of pore structure, and the high thermal conductivity characteristics of its own solid skeleton to achieve effective encapsulation and support of phase change materials. At present, there is no research report on the use of geopolymer microspheres as carriers for the preparation of composite phase change heat storage materials.

[0006] The present invention uses lithium slag to prepare geopolymer microspheres with a porous structure, and uses nano-graphite, carbon nano, graphene and other high thermal conductivity materials as thermal conductivity modifiers to enhance the heat transfer effect of the geopolymer microspheres. Then, the prepared geopolymer microspheres are used to encapsulate organic phase change materials to prepare shaped composite phase change heat storage materials, which is not only of great significance for the resource utilization of lithium slag and solving environmental problems, but also expected to play an important role in the field of new energy materials. Summary of the invention

[0007] In the present invention, lithium slag-based polymer microspheres are first prepared, and then compounded with phase change heat storage materials to prepare composite phase change energy storage materials of lithium slag-based polymer microspheres / organic phase change materials, thereby greatly improving the heat transfer performance and thermal stability of the composite phase change materials. In addition, 0.5% of graphite can be added to lithium slag to prepare graphite-modified lithium slag-based polymer microspheres to improve the thermal conductivity of the composite phase change energy storage materials.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] Lithium slag-based polymer microspheres------------------------30wt%~50wt%

[0010] Phase change material------------------------------------------50wt%~70wt%

[0011] Among them, the phase change material is characterized in that the phase change material is an organic phase change material or an inorganic phase change material or an organic and inorganic composite phase change material, organic phase change materials such as paraffin, stearic acid, lauric acid, polyols, etc.; inorganic phase change materials such as CaCl2·6H2O, Na2SO4·10H2O, MgCl2·6H2O, Al(NO3)3·6H2O, etc.; the phase change material can be one of them, or a combination of any several of them.

[0012] The present invention also relates to a method for preparing the above-mentioned lithium slag-based composite phase-change energy storage material, wherein the preparation method and its characteristics are:

[0013] Step 1: Add 12 to 16 parts by mass of lithium slag, 1 to 4 parts by mass of thermal conductivity modifier and 6 to 10 parts by mass of water to 15 to 20 parts by mass of 10 to 13 mol / L NaOH solution, stir evenly, add 6 to 10 drops of H2O2 solution with a concentration of 10wt% to 30wt%, and stir for 1 minute at a rotation speed of 500 to 1000 r / min to form a uniform slurry. It should be noted that, in this system, if the concentration and quality of the NaOH solution and the quality of the lithium slag are too high or too low, the viscosity of the slurry will be correspondingly high or low, which is not conducive to the molding of the microspheres; the addition of H2O2 solution is to foam and form more pores in the microspheres. If too much H2O2 solution is dripped, it will be not conducive to molding, and the strength of the obtained material will be low and cannot be used; if too little H2O2 solution is dripped, the porosity of the geopolymer will be low, thereby reducing the loading effect of the geopolymer microspheres; wherein the thermal conductivity modifier can be one or a combination of nano-graphite, carbon nanotubes, and graphene, because carbon-based nanomaterials are mainly non-polar, which is conducive to the dispersion of bubbles in the balls. Too much addition is not conducive to molding, and too little addition will result in poor thermal conductivity.

[0014] Step 2: Use a rubber-tipped dropper to uniformly drop the slurry of step 1 at a rate of 50 to 90 drops per minute into silicone oil with a temperature of 70 to 85° C. and a viscosity of 1000 cs to 2000 cs, which is stirred at a speed of 600 to 1200 r / min. After the dropped slurry is dispersed into microspheres by the silicone oil and solidified, the whole is placed in an oven at 75 to 90° C. for curing for 24 to 72 hours. In this step, it should be noted that if the slurry is dripped in too fast, adhesion will occur, and if the dripping speed is too slow, the temperature of the silicone oil will decrease, thereby reducing the sphericity; when the silicone oil temperature is too low, the alkali-induced reaction rate will decrease, which is not conducive to the molding of the geopolymer microspheres; when the silicone oil temperature is too high, the reaction components dissolved in the early stage will quickly depolymerize and condense to form geopolymer gel covering the unreacted raw material particles, which is not conducive to further alkali-induced reaction; when the viscosity of the silicone oil is too high or too low, it is not conducive to the molding of lithium slag-based polymer microspheres; the prepared lithium slag-based polymer microspheres must be spherical in shape, with a particle size of preferably 100 to 400 μm and a pore size of preferably 0 to 10 nm; this is because, when the sphericity is not good, the loading effect on the phase change material will be reduced, and when the particle size or pore size of the geopolymer microspheres is too large, leakage is likely to occur, and when the particle size is too small, the loading efficiency of the phase change material will be affected.

[0015] Step 3, filtering out the microsphere product obtained in step 2, washing with 75%-95% ethanol solution, and drying at 120° C. for 4-8 hours to remove the silicone oil adhering to the surface;

[0016] Step 4, calcining the product obtained after drying in step 3 at 500° C. for 1-5 hours to fully remove excess silicone oil on the surface and internal pores of the microspheres;

[0017] Step 5, loading an excess of phase change material into a load device, and completely melting it within a temperature range of 10-20°C above the melting temperature of the selected phase change energy storage material; completely immersing the geopolymer microspheres obtained in step 4 into a device containing excess molten liquid phase change material, under the conditions of a device pressure of -0.05 to -0.1 MPa and a temperature of 60 to 150°C, the specific temperature is adjusted according to the phase change material itself, and continuously pumping with a vacuum pump for 15 to 30 minutes, then turning off the vacuum pump and maintaining this state for 2 to 4 hours, so that the melted phase change material fully enters the pores of the geopolymer microspheres, and opening the vent valve to restore the internal pressure of the vacuum device to normal, thereby preliminarily obtaining a composite phase change energy storage material;

[0018] Step 6: Place the product obtained in step 5 on filter paper and perform leakage treatment in an oven at a temperature near the phase change temperature point of the phase change material to remove excess phase change material that is not stably encapsulated in the geopolymer microspheres. Replace the filter paper continuously until obvious marks appear on the filter paper. After the treatment is completed, a composite phase change energy storage material product with lithium slag-based geopolymer microspheres as a carrier can be obtained.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] In the present invention, a new method for utilizing spodumene tailings resources for lithium extraction is provided; on this basis, the surface area of ​​the prepared geopolymer microspheres is 11.36m 2 / g, the average pore size is 28.376nm, the pore structure is rich, and it has excellent packaging ability; the composite phase change energy storage material prepared by graphite-modified lithium slag-based polymer microspheres has excellent heat storage performance, significantly improved thermal conductivity and significantly improved stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a stereoscopic photograph of the lithium slag-based polymer microspheres used in Example 1;

[0022] Figure 2 The mercury intrusion curve pore size distribution and cumulative graph of the lithium slag-based polymer microspheres used in Example 1;

[0023] Figure 3 The XRD patterns of the composite phase change energy storage prepared in Examples 1 and 2;

[0024] Figure 4 The infrared spectra of the composite phase change energy storage prepared in Examples 1 and 2;

[0025] Figure 5 Thermal analysis curves of the composite phase change energy storage materials prepared in Examples 1 and 2. DETAILED DESCRIPTION

[0026] Example 1: Example of preparing composite phase change heat storage material by loading polyethylene glycol 4000 with geopolymer microspheres

[0027] (1) Geopolymer microspheres were prepared by the dispersion suspension method. 20 g of lithium slag and 12 g of water were added to 25 g of 11 mol / L NaOH solution, and the mixture was stirred evenly. Then, 8 drops of H2O2 solution were added, and the mixture was stirred at 1000 r / min for 1 min to form a uniform slurry. Next, the slurry was quickly dripped into 85°C silicone oil stirred at 800 r / min at a rate of 60 drops per minute. The slurry was dispersed into microspheres and solidified rapidly under the shear force of the silicone oil. The silicone oil dripped into the slurry was then placed in an oven at 85°C for curing for 72 h. The resulting product was filtered, washed, dried at 120°C for 8 h, and then calcined at 500°C for 5 h to remove excess silicone oil on the surface and internal pores of the microspheres. Finally, the geopolymer microspheres of 100 to 400 μm were obtained by sieving.

[0028] (2) loading an excess amount of polyethylene glycol 4000 into a loading device and melting it at a temperature of 70° C.

[0029] (3) The treated geopolymer microspheres are completely immersed in a liquid phase device containing excess molten polyethylene glycol 4000, placed in a vacuum drying oven, and continuously vacuumed for 15 minutes at 70°C. After being allowed to stand for 2 hours at -0.09 MPa and 70°C, they are taken out;

[0030] (4) Leakage: The sample was placed on filter paper and tested for leakage in an oven at 85°C. During this process, the filter paper was continuously replaced until no more polyethylene glycol 4000 was precipitated, and finally the prepared geopolymer microsphere-polyethylene glycol 4000 composite phase change energy storage material was obtained.

[0031] The performance indicators of the obtained samples are as follows: The pore structure and pore size distribution of the treated lithium slag-based polymer microspheres are as follows: Figure 1 and Figure 2 As shown in the figure, it can be observed that the prepared geopolymer microspheres have good sphericity and uniform particle size distribution (100-400 μm). The pore size of the microspheres is mainly distributed in the range of 0-10 nm, with microporous and mesoporous structures. In addition, there are a few macropores, and the specific surface area is 11.36 m 2 / g, the average pore size is 28.376nm. The X-ray diffraction results of the encapsulated samples are as follows Figure 3 As shown in Figure 2, the physical phases of the sample are LiAlSi2O6 and polyethylene glycol 4000, indicating that polyethylene glycol 4000 is successfully loaded into the lithium slag-based polymer microspheres; the infrared spectrum results of the encapsulated sample are shown in Figure 2. Figure 4 As shown in the figure, the infrared spectrum of the sample mainly comes from lithium slag and polyethylene glycol 4000, indicating that polyethylene glycol 4000 is successfully loaded in the lithium slag-based polymer microspheres; the loading rate of lithium slag-based polymer microspheres for polyethylene glycol 4000 is 42.16%, its melting latent heat is 79.28 J / g, and the solidification latent heat can reach up to 71.84 J / g. The prepared material is tested by a heat flow meter thermal conductivity tester, and the thermal conductivity of the obtained sample is 0.0611 W·m -1 ·K -1 .

[0032] Example 2: Example of preparing composite phase change heat storage material by loading polyethylene glycol 4000 with graphite modified geopolymer microspheres

[0033] (1) Preparation of microspheres: Add 20g of lithium slag, 0.45g of graphite and 12g of water to 25g of 11mol / L NaOH solution, stir evenly, add 8 drops of H2O2 solution, and stir for 1min at a speed of 1000r / min to make a uniform slurry. Next, quickly drip the slurry at a rate of 60 drops per minute into 85℃ silicone oil stirred at a speed of 800r / min. The slurry is dispersed into microspheres and quickly solidified under the shear force of the silicone oil. Then, the silicone oil dripped into the slurry is placed in an oven at 85℃ for curing for 72h. The resulting product is filtered, dried at 120℃ for 8h, and calcined at 500℃ for 5h to remove excess silicone oil on the surface and internal pores of the microspheres. Finally, the graphite-modified geopolymer microspheres of 100-400μm are sieved;

[0034] (2) loading an excess amount of polyethylene glycol 4000 into a loading device and melting it at a temperature of 70° C.

[0035] (3) The treated graphite-modified geopolymer microspheres are completely immersed in a liquid phase device containing excess molten polyethylene glycol 4000, placed in a vacuum drying oven, and continuously vacuumed for 15 minutes at 70°C, and then allowed to stand for 2 hours at -0.09 MPa and 70°C before being taken out;

[0036] (4) Leakage: The sample was placed on filter paper and tested for leakage in an 85°C oven. During this process, the filter paper was continuously replaced until no more polyethylene glycol 4000 was precipitated. Finally, the prepared graphite-modified geopolymer microsphere-polyethylene glycol 4000 composite phase change energy storage material was obtained.

[0037] The performance indicators of the obtained samples are as follows: the loading rate of graphite-modified geopolymer microspheres on polyethylene glycol 4000 is 42.16%, the maximum latent heat of melting can reach 79.28 J / g, and the maximum latent heat of solidification can reach 71.84 J / g. By using graphite to enhance the heat transfer effect of geopolymer microspheres, the overall thermal conductivity of geopolymer microspheres was successfully increased by 46.15% to 0.0893 W·m-1·K-1.

[0038] In summary, the present invention uses lithium slag to prepare geopolymer microspheres and graphite-modified geopolymer microspheres as carriers, and prepares composite phase change energy storage materials by loading phase change materials. The porous spherical structure phase change material prepared by vacuum impregnation has a high loading rate, excellent thermal stability, good thermal conductivity, high melting latent heat, high solidification latent heat, etc.

[0039] The present invention is described in detail above in combination with preferred embodiments and exemplary examples. However, it should be noted that these specific embodiments are only illustrative explanations of the present invention and do not constitute any limitation on the protection scope of the present invention. Without exceeding the spirit and protection scope of the present invention, various improvements, equivalent substitutions or modifications may be made to the technical content of the present invention and its embodiments, which all fall within the protection scope of the present invention. The protection scope of the present invention shall be subject to the attached claims.

Claims

1. A composite phase change energy storage material with lithium slag-based polymer microspheres as carrier, characterized in that The invention comprises the following raw materials in parts by weight: Lithium slag-based polymer microspheres-----------------------------30wt%~50wt%, Phase change material------------------------------------------50wt%~70wt%.

2. The composite phase change energy storage material with lithium slag-based polymer microspheres as carrier according to claim 1, characterized in that: The lithium slag-based polymer microspheres are spherical in shape, with a particle size of 100-400 μm and a pore size of 0-10 nm.

3. The composite phase change energy storage material with lithium slag-based polymer microspheres as carrier according to claim 2, characterized in that: The phase change material is an organic phase change material or an inorganic phase change material or an organic and inorganic phase change material, wherein the organic phase change material is selected from paraffin, stearic acid, lauric acid, and polyols; the inorganic phase change material is selected from CaCl2·6H2O, Na2SO4·10H2O, MgCl2·6H2O, and Al(NO3)3·6H2O; the phase change material can be one of them or any combination of several of them.

4. The method for preparing a composite phase change energy storage material with lithium slag-based polymer microspheres as a carrier according to any one of claims 1 to 3, characterized in that Lithium slag, thermal conductivity modifier, NaOH solution and H2O2 solution are used as raw materials to prepare lithium slag-based polymer microspheres through a dispersion suspension method, and a phase change material is encapsulated by vacuum impregnation to obtain a composite phase change energy storage material; wherein the thermal conductivity modifier can be one or a combination of nano-graphite, carbon nanotubes and graphene.

5. The method for preparing lithium slag-based polymer microspheres according to claim 4, characterized in that The following steps are involved: Step 1.1, add 12 to 16 parts by mass of lithium slag, 1 to 4 parts by mass of thermal conductivity modifier and 6 to 10 parts by mass of water to 15 to 20 parts by mass of 10 to 13 mol / L NaOH solution, stir evenly, add 6 to 10 drops of H2O2 solution with a concentration of 10wt%-30wt%, stir at a speed of 500-1000r / min for 1 minute to form a uniform slurry; Step 1.2, using a rubber-tipped dropper, uniformly drip the slurry of step 1 at a rate of 50 to 90 drops per minute into silicone oil with a temperature of 70 to 85° C. and a viscosity of 1000 cs to 2000 cs, which is stirred at a speed of 600 to 1200 r / min. After the dripped slurry is dispersed into microspheres by the silicone oil and solidified, the whole is placed in an oven at 75 to 90° C. for curing for 24 to 72 hours; Step 1.3, filtering out the microsphere product obtained in step 2, washing with 75%-95% ethanol solution, and drying at 120° C. for 4-8 hours to remove excess silicone oil on the surface of the microspheres; Step 1.4, calcining the lithium slag-based polymer microspheres obtained after drying in step 3 at 500° C. for 5 h to remove excess silicone oil on the surface and internal pores of the microspheres, and finally obtaining lithium slag-based polymer microspheres.

6. The method for preparing the composite phase change energy storage material according to claim 4, characterized in that The following steps are involved: Step 2.1, loading an excess of phase change material into a load device, and completely melting it within a temperature range of 10-20°C above the melting temperature of the selected phase change energy storage material; completely immersing the obtained geopolymer microspheres in a device containing excess molten liquid phase change material, under the environmental conditions of a device pressure of -0.05 to -0.1 MPa and a temperature of 60 to 150°C, the specific temperature is adjusted according to the phase change material itself, and continuously pumping with a vacuum pump for 15 minutes, turning off the vacuum pump and maintaining this state for 2 hours, so that the melted phase change material is fully introduced into the pores of the microspheres, and opening the vent valve to restore the internal pressure of the vacuum device to normal, thereby preliminarily obtaining a composite phase change energy storage material; Step 2.2, place the product obtained in step 1 on filter paper, and perform leakage treatment in an oven at a temperature near the phase change temperature point of the phase change material, remove excess phase change material that is not stably encapsulated in the geopolymer microspheres, and continuously replace the filter paper until there are no obvious marks on the filter paper. After the treatment is completed, a composite phase change energy storage material product with lithium slag-based geopolymer microspheres as a carrier can be obtained.

Citation Information

Patent Citations

  • Porous geopolymer-based phase-change energy storage material

    CN103641433A

  • Large-volume lithium slag waste comprehensive utilization technology and implementation method thereof

    CN111302708A

  • Geopolymer composite phase-change material suitable for road subgrade as well as preparation method and application thereof

    CN112048284A

  • Hierarchical pore structure carrier composite phase change energy storage material and preparation method thereof

    CN114716978A

  • Porous geopolymer foaming phase change energy storage material and preparation method thereof

    CN114853396A

Cited By

  • Comprehensive recovery method of lithium slag

    CN120714773A

  • Composite geopolymer energy storage material, preparation method and application thereof

    CN121107766A

  • All-solid waste cementing material-based low-carbon low-heat high-crack-resistance mass concrete

    CN121517149A